FUNGSI PENGAWASAN MAHKAMAH AGUNG DALAM PENYELENGGARAAN PERADILAN YANG IMPARSIAL - Sampara, Said (Fakultas Hukum, Universitas Muslim Indonesia, 2017)
Implementation of judicial power in the realization of judicial impartiality rests on their independence and the independence of judiciary in performing the duties of his judicial is not affected by any power, as well as the responsibilities imposed on judges in carrying out the task of checking and deciding cases and functions of the Supreme Court under the supervision of the judiciary the impartiality in the administration of judicial power, manifested in the form of preventive supervision, in the form of signs norms enshrined in both the legislation and the code of ethics and code of conduct of judges. In addition, there are forms of repressive supervision which in practice is carried out by the Supreme Court and the Judicial Commission. Abstrak Implementasi kekuasaan kehakiman dalam perwujudan imparsialitas yudisial bertumpu pada independensi mereka dan independensi kehakiman dalam menjalankan tugas-tugas kehakimannya tidak dipengaruhi oleh kekuasaan apa pun, serta tanggung jawab yang dibebankan pada hakim dalam melaksanakan tugas memeriksa dan memutuskan kasus dan fungsi Mahkamah Agung di bawah pengawasan pengadilan, ketidakberpihakan dalam administrasi kekuasaan kehakiman, yang diwujudkan dalam bentuk pengawasan preventif, dalam bentuk tanda-tanda norma yang diabadikan baik dalam undang-undang dan kode etik serta kode perilaku hakim. Selain itu, ada bentuk pengawasan represif yang dalam praktiknya dilakukan oleh Mahkamah Agung dan Komisi Yudisial.